Strengthening School-Family Partnerships Through Seminars on the Detection of Children's Characteristics, Potential and Talents: Penguatan Kemitraan Sekolah-Keluarga Melalui Seminar Deteksi Karakteristik, Potensi, dan Bakat Anak - Sumiati, Sumiati; Komariah, Aan; Kurniady, Dedy Achmad; Suryana, Asep; Amin, Arip (Universitas Lancang Kuning, 2024)
The activity is a seminar for the detection of the characteristics, potential, and talents of children that is part of the strengthening of the school-family partnership. This is a part of an effort to raise awareness among parents of the importance of understanding the child especially in the characteristic, potential and talent that can be a reference in decision-making of the educational processes carried out both in the family and in the school. The implementation of this training is going well even though some audiences need to follow up in understanding and applying the concepts presented by the examiner. As a result of this activity, the seminar participants consisting of the parents of elementary school students in Randegan Wetan Village and some representatives of local primary school teachers were able to emulate the basic theory of detection of characteristics, potential, and children's talents